CULTURAL PRODUCTION STRATEGIES THROUGH LOCAL WISDOM ORAL TRADITIONS PERDUKUHAN NGINO XII SLEMAN YOGYAKARTA (STRATEGI PRODUKSI KULTURAL MELALUI KEARIFAN LOKAL TRADISI LISAN MASYARAKAT PERDUKUHAN NGINO XII SLEMAN YOGYAKARTA) - Lastry Monika; Nur Ahmad Salman Herbowo (Jurnal Gramatika, 2020)
This study uses oral traditions contained in Ngino XII hamlet, Margoagung, Seyegan District, Sleman Regency, Yogyakarta as material objects and Pierre Bourdieu's genetic structuralism theory as formal objects. This research is based on the assumption that the oral traditions that exist in the Ngino XII hamlet are seen as legitimating tools to realize the cultural identity of the people concerned. Therefore, the analysis in this study aims to determine and analyze the local wisdom of the oral tradition as a cultural production strategy in realizing the cultural identity of the Ngino XII hamlet. The results showed that the Ngino XII hamlet community was a dominated agent to carry out the traditions they had inherited. This tradition lasts from generation to generation because the habitus of each dominant agent is the same. In addition, the existence of cultural capital and social capital serve as a cultural production strategy that makes Ngino XII has its own unique cultural traditions or identities that are unique and different from the traditions of other regions. Using the theory put forward by Bourdieu about the arena of cultural production, it can be found that a subculture exists with certain goals, one of which is to form cultural identity. This indicates that research on oral traditions or oral literature is becoming more diverse.